Mediation Role of Locus of Control on the Relationship of Learned-helplessness and Academic Procrastination among College Students in Penang, Malaysia. - Kususanto Prihadi; Christine Y.H. Tan; Reimy T.S. Tan; Poh Ling Yong; Jonathan H.E Yong; Sharvini Tinagaran; Chee Leong Goh; Yu Jin Tee (Institute of Advanced Engineering and Science, 2018)
This study aims to study the mediation role of locus of control on the impact of learned helplessness on students’ academic procrastination. Studies reported that more than 70% university students procrastinate, and one of the causes is the perception that one is vulnerable or helpless in finishing the procrastinate tasks. It was hypothesized that internal locus of control iLOC can reduce the effect if the learned helplessness (LH) on academic procrastination. Data was collected from 60 university students by utilizing instruments such as Duttweiller’s Internal Control Scale, Pure Procrastination Scale (adapted for academic setting) and Learned Helplessness Scale. Multiple regression with Process add-on showed that full mediation occurred; the prediction of LH on procrastination became insignificant when iLOC is controlled. In other words, when students believe that they are in control of their events, the less likely they will procrastinate doing their tasks due to helpless feeling.